2019
DOI: 10.1017/s0025315419000481
|View full text |Cite
|
Sign up to set email alerts
|

Shell variations in the gastropod,Monodonta labio, in the North-western Pacific: the important role of temperature in the evolution process

Abstract: Molluscan shells showing phenotypic variations are ideal models for studying evolution and plasticity. In north-eastern Asia, genetic and morphological diversity of the gastropod, Monodonta labio, were assumed to be influenced by both palaeoclimatic changes and current ecological factors. In this study, we examined spatial variations in shell shape of M. labio using general measurement and geometric morphometric analysis. We also investigated whether shell shape variation is best explained by environmental gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…The GM-based methods are widely applied to investigate variation in the shape of gastropod shells. The main fields of application include the study of intraspecific variability (Vuolo et al, 2011;Madeira et al, 2012;Moneva et al, 2012b;Sepúlveda and Ibáñez, 2012;Vogler et al, 2012;Avaca et al, 2013;Camama et al, 2014;Jamasali et al, 2014;Sobrepeña and Demayo, 2014;Cazenave and Zanatta, 2016;Zhao et al, 2019;Tuset et al, 2020) and assessment of environmental impacts (Sepúlveda and Ibáñez, 2012;Vogler et al, 2012;Vasallo et al, 2013;Camama et al, 2014;Cazenave and Zanatta, 2016;Amini-Yekta et al, 2019;Zhao et al, 2019), including the effect of pollution (Márquez et al, 2011;Abdelhady, 2016;Primost et al, 2016). Nevertheless, GM was also used for identification of mollusks (Doyle et al, 2018), evaluation of interspecific variability (Dommergues et al, 2003;Carvajal-Rodríguez et al, 2005;Vuolo et al, 2011;Cruz et al, 2012;Vogler et al, 2012;Silos et al, 2014;Becker et al, 2016;Miller, 2016), ontogenetic and individual variation (Moneva et al, 2012a;Avaca et al, 2013;Sobrepeña and Demayo, 2014), and to characterize phylogenetic relationships (Smith and Hendricks, 2013;…”
Section: Shellsmentioning
confidence: 99%
See 2 more Smart Citations
“…The GM-based methods are widely applied to investigate variation in the shape of gastropod shells. The main fields of application include the study of intraspecific variability (Vuolo et al, 2011;Madeira et al, 2012;Moneva et al, 2012b;Sepúlveda and Ibáñez, 2012;Vogler et al, 2012;Avaca et al, 2013;Camama et al, 2014;Jamasali et al, 2014;Sobrepeña and Demayo, 2014;Cazenave and Zanatta, 2016;Zhao et al, 2019;Tuset et al, 2020) and assessment of environmental impacts (Sepúlveda and Ibáñez, 2012;Vogler et al, 2012;Vasallo et al, 2013;Camama et al, 2014;Cazenave and Zanatta, 2016;Amini-Yekta et al, 2019;Zhao et al, 2019), including the effect of pollution (Márquez et al, 2011;Abdelhady, 2016;Primost et al, 2016). Nevertheless, GM was also used for identification of mollusks (Doyle et al, 2018), evaluation of interspecific variability (Dommergues et al, 2003;Carvajal-Rodríguez et al, 2005;Vuolo et al, 2011;Cruz et al, 2012;Vogler et al, 2012;Silos et al, 2014;Becker et al, 2016;Miller, 2016), ontogenetic and individual variation (Moneva et al, 2012a;Avaca et al, 2013;Sobrepeña and Demayo, 2014), and to characterize phylogenetic relationships (Smith and Hendricks, 2013;…”
Section: Shellsmentioning
confidence: 99%
“…Despite the fact that landmarkbased GM has been used in studies of gastropod mollusks for about 30 years (Johnston et al, 1991), this method truly flourished only during the last decade, when the development of imaging technologies improved the quality and resolution of digital images, allowing for a sufficient number of landmarks to be distinguished in the images. In a number of studies (Moneva et al, 2012b;Sepúlveda and Ibáñez, 2012;Zhao et al, 2019), environmental factors determining such variability were analyzed. Zhao et al (2019) indicated that temperature was the key environmental factor determining the variability of the Monodonta labio shell.…”
Section: Shellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphologically, this species is characterized by a highly pointed apex and prominent granules on the spiral ribs. Shell color is highly variable, with a typically yellowish brown, greenish, or reddish background (Zhao et al 2019). Found on sediment surface in the mid intertidal zone.…”
Section: Family Of Trochidaementioning
confidence: 99%
“…These relatively protected conditions cause the sizes of the length, width, and height of the shell of M. annulus to be relatively similar. The same environmental conditions and geographical locations made the shells of gastropods have the same structure and shape (Trussell 1997;Tissot 1984;Cazenave and Zanatta 2016;Zhao et al 2019). In addition, variations of the shapes of gastropods shells are influenced by the body size and the sex differences (Avaca et al 2013).…”
Section: Difference In Length Width and Height Of Shell Blotch Lenmentioning
confidence: 99%